Efficiency Recipe: Optimization of Online-Offline Sales Combination for Maximum Net Profit of Gado-Gado MSMEs with the Simplex Method - Indri Susilowati; Putri Jhahrotul Fitriana; Rifka Marako Nita; Laraib Aftab Khokhar (Journal of Teaching and Learning Mathematics, 2026)
This study aims to determine the production combination that produces maximum net profit in hodgy MSMEs through the application of the Simplex method on a linear program model. A quantitative approach with a case study was carried out on one hodgepodge MSME that sells online and offline. The model is formulated with two decision variables (number of online and offline portions) and four constraints: maximum number of portions (50 portions), service time (max. 450 minutes/day), gross profit (max. IDR 300,000), and the selling price. Data were collected through interviews, observations, and documentation. The optimization results showed that the optimal solution was achieved in the production of 50 offline portions and 0 online portions, with a maximum net profit of IDR 300,000 per day. These findings confirm that service time efficiency (offline: 5 minutes/portion vs online: 7 minutes/portion) is the dominant determining factor in production decisions, even though online selling prices are higher. Research proves that the Simplex method is effective in helping MSMEs make rational and data-driven production decisions